Degradation of sugarcane bagasse for ethanol fermentation and utilization of chemicals and biologically active compounds - Duy Khuong, Le (College of Engineering, University of the Philippines Diliman, 2014)
The oil demand for energy and transportation applications has been increasing tremendously over the past decades as the world population grew, and globally developed economics. One solution for supplying high consumption is the blend of ethanol-gasoline. As a result, the ethanol consumption has been increasing globally. It is extremely essential to develop methods of bioprocesses and exploited material completely that may reduce cost associated with lignocellulosic ethanol production. This dissertation at first indicated that mild alkaline pretreatment coupled with consolidated bioprocessing offer a promising bioprocess for ethanol production from sugarcane bagasse without the addition of commercial enzymes. Second, integrated fungal fermentation proved that these sequential procedures are potentially applicable to convert sugarcane bagasse into ethanol using single fungus. It is believed that IFFP are suitable for various other lignocellulosic materials (i.e. softwood, rice straw, corn crops) and could contribute in environmentally, economical and technological friendlier fuel ethanol production. Additionally, the waste of NaOH pretreatments was proved have valuable chemicals, it makes alkaline pretreatments become more economically feasible. Finally, the high value added chemicals identified from sugarcane bagasse indicated that we could make a biorefinery of fuel ethanol and value chemicals from lignocellulosic materials.